Cytotoxic Effect of Five Medicinal Plants Extracts Using Brine Shrimp (Artemia salina) TEST (Bangladesh Journal of Scientific and Industrial Research, 2012)
Medicinal plants like Curcuma longa, Curcuma zedoaria, Streblus asper, Enhydra fluctunas and Scoparia dulcis are commonly available in   Bangladesh. This study investigated the effect of ethanol extracts from these five medicinal plants on the viability of Brine Shrimp larvae.   The lethal concentrations (LC50 values) of the extracts were determined. LC50 values of C. longa, C. zedoaria and S. asper were less than   250?g/ml and that of E. fluctunas was greater than 250 ?g/ml. Among five plants tested, one (S. dulcis) appear to be inactive. Results indicate   that C. longa, C. zedoaria and S. asper could be potential sources of bio-active compounds DOI: http://dx.doi.org/10.3329/bjsir.v47i1.10724 Bangladesh J. Sci. Ind. Res. 47(1), 133-136, 2012